Regulatory measures for distressed insurance undertakings: a comparative study. Issue 1 (2nd January 2020) - Chen, An; Hieber, Peter; Lämmlein, Lars
ABSTRACT: In Europe, the introduction of the regulatory scheme Solvency II wants to improve the risk management practice in insurance undertakings. One aspect of the new regulatory rules is an improved supervision of distressed insurance undertakings. In case the insurance undertaking is in financial distress, the regulator may force it to take appropriate precautionary measures to avoid bankruptcy. In this article, we compare the two most common regulatory measures in case of distress: A decrease of the asset investment risk and contingent equity capital. In a Black-Scholes-Merton economy, we model the insurance undertaking's assets and liabilities by a structural default model. We consider a regulator acting in the interests of the policyholder and analyze the effect of the regulatory measures on the policyholder's benefits. We find that the contingent equity capital seems more efficient in terms of increasing the benefits of the policyholders.